2010
DOI: 10.1074/jbc.m109.096743
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of an Arylalkylamine-N-acetyltransferase, Bm-iAANAT, Are Responsible for Silkworm Melanism Mutant

Abstract: Coloration is one of the most variable characters in animals and provides rich material for studying the developmental genetic basis of pigment patterns. In the silkworm, more than 100 gene mutation systems are related to aberrant color patterns. The melanism (mln) is a rare body color mutant that exhibits an easily distinguishable phenotype in both larval and adult silkworms. By positional cloning, we identified the candidate gene of the mln locus, Bm-iAANAT, whose homologous gene (Dat) converts dopamine into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(78 citation statements)
references
References 35 publications
5
73
0
Order By: Relevance
“…Mapping of stony locus and bioinformatic analysis of candidate regions were performed, as described previously (Dai et al 2010). In Bm_nscaf2827 (chromosome 8), we identified polymorphic PCR markers between the parents, Dazao-stony and C108, and assessed these in BC 1 F individuals.…”
Section: Positional Cloningmentioning
confidence: 99%
See 1 more Smart Citation
“…Mapping of stony locus and bioinformatic analysis of candidate regions were performed, as described previously (Dai et al 2010). In Bm_nscaf2827 (chromosome 8), we identified polymorphic PCR markers between the parents, Dazao-stony and C108, and assessed these in BC 1 F individuals.…”
Section: Positional Cloningmentioning
confidence: 99%
“…Quantitative RT-PCR was performed as described previously (Dai et al 2010), using the StepOneTM real-time PCR xystem (ABI). Primers used for qRT-PCR are listed in Table S1.…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…EU378921, KF246473-KF246476, KF290562, BK008791, and BK008792). The AANAT family that is the subject of the current report is distinct from another family also named AANAT, which includes enzymes involved in acetylation of dopamine and other arylalkylamines in insects (11,12). These two protein families are only distantly related to each other, although both belong to the GCN5 superfamily of acetyltransferases.…”
mentioning
confidence: 94%
“…Recently, the mln mutant, which exhibits a readily distinguishable phenotype in both the larvae and adults, was characterised at the molecular level based on positional cloning and functional analysis (Dai et al, 2010;Zhan et al, 2010). Linkage analysis and genomic studies have shown that Bombyx arylalkamine-N-acetyl transferase, the homologous gene (Dat) that converts dopamine into N-acetyl dopamine, encodes a precursor of N-acetyl dopamine, sclerotin in Drosophila and it is the gene responsible for mln (Dai et al, 2010;Zhan et al, 2010). However, other causal genes have not yet been identified.…”
Section: Introductionmentioning
confidence: 99%